Flat sticker as a mobile airway foreign body: A case report and review of the literature - Robert E. Wineski, MD; Emma C. Panico, MD; Luke N. Bailey, MD; Agustin M. Cardenas, MD; Jessica W. Grayson, MD; Brian J. Wiatrak, MD (Radiology Case Reports, 2020)
Diagnosis of an airway foreign body in the setting of an unwitnessed aspiration event remains a challenge for physicians in the emergency setting. We describe a case of a 2-year-old male who presented to the emergency department with atypical symptoms resulting from ingestion and aspiration of a large, flat sticker. The airway foreign body remained in place for over 24 hours despite obtaining appropriate airway imaging, and the object was later removed without complication via rigid bronchoscopy in the operating room. Further review of this case and the current literature highlighted multiple lessons. Initial evaluations should combine a rigorous history and physical with strict guidelines on usage of multiple imaging modalities (eg, plain radiographs and CT). Imaging should be obtained with the patient devoid of all obstructive materials in multiple positions (eg, upright, supine, lateral) in order to maximize the physician's ability to positively diagnose airway foreign bodies prior to definitive treatment with rigid bronchoscopy.